1993
DOI: 10.1172/jci116831
|View full text |Cite
|
Sign up to set email alerts
|

Charge selectivity of the glomerular filtration barrier in healthy and nephrotic humans.

Abstract: We used dextran sulfate (DS) to evaluate barrier charge selectivity in 11 nonproteinuric subjects and in 11 patients with the nephrotic syndrome due to either membranous nephropathy or minimal change nephropathy. The 3H-DS preparation spanned a molecular radius interval of 10-24A and exhibited size-dependent protein binding in vitro. Urine and ultrafiltrates of plasma were separated by size into narrow fractions using gel permeation chromatography. The sieving coefficient (0) for ultrafilterable DS of 15A radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
90
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(97 citation statements)
references
References 36 publications
(46 reference statements)
6
90
0
1
Order By: Relevance
“…[30][31][32][33][34][35][36][37] However, in all of these studies albuminuria was not markedly increased, thus supporting recent evidence for other mechanisms having an active role in albumin retrieval occurring in PTCs. FcRn, the only albumin transcytotic receptor yet identified, is concentrated in the apical region of the PTCs as shown in Figure 4B.…”
Section: Discussionsupporting
confidence: 82%
“…[30][31][32][33][34][35][36][37] However, in all of these studies albuminuria was not markedly increased, thus supporting recent evidence for other mechanisms having an active role in albumin retrieval occurring in PTCs. FcRn, the only albumin transcytotic receptor yet identified, is concentrated in the apical region of the PTCs as shown in Figure 4B.…”
Section: Discussionsupporting
confidence: 82%
“…The glomerular barrier restricts the passage of anionic macromolecules relative to uncharged molecules of similar size and configuration. 46 Previous studies showed that the charge selectivity resides mainly at endothelial cells or podocytes rather than the GBM, 47,48 and a more recent study has shown that endothelial cell glycocalyx, a negatively charged surface layer of membrane-associated proteoglycans and glycosaminoglycans, is a critical determinant in glomerular charge selectivity. 31 Furthermore, Arcos et al 28 showed that chronic NO inhibition using an NO inhibitor impairs glomerular endothelial charge barrier and causes albuminuria and GBM thickening.…”
Section: Discussionmentioning
confidence: 99%
“…2 The underlying pathologic change responsible for proteinuria in various glomerular diseases is the loss of size-selective and/or charge-selective properties of the glomerular filtration barrier. [3][4][5][6][7] The glomerular filtration barrier is composed of three layers: A fenestrated endothelial layer, a glomerular basement membrane (GBM), and podocyte foot processes connected by a slit diaphragm. Traditionally, the GBM has been considered a coarse filter that restricts large molecules, whereas the slit diaphragm was thought to function as a fine filter that contributes to ultimate size selec-tivity, permitting permeability only to molecules that are smaller than albumin.…”
mentioning
confidence: 99%